2017
DOI: 10.4102/jamba.v9i1.350
|View full text |Cite
|
Sign up to set email alerts
|

Climate change: A threat towards achieving ‘Sustainable Development Goal number two’ (end hunger, achieve food security and improved nutrition and promote sustainable agriculture) in South Africa

Abstract: This article aims to assess the impacts of climate change towards the achievement of Sustainable Development Goal number two (SDG 2) as well as examining the poverty alleviation strategies by subsistence farmers in South Africa. Widespread hunger and poverty continue to be among the most life-threatening problems confronting mankind. Available statistics show that global poverty remains a serious challenge around the world. Across the globe, one in five people lives on less than $1 a day and one in seven suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 13 publications
1
67
0
6
Order By: Relevance
“…Without these interventions, climate change will likely worsen the country’s existing socioeconomic and health inequities [ 22 ]. A step-change is required in the country’s response if it is to meet its commitments to the Sustainable Development Goal 2, which includes improved food security and improved nutrition, and sustainable agriculture [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without these interventions, climate change will likely worsen the country’s existing socioeconomic and health inequities [ 22 ]. A step-change is required in the country’s response if it is to meet its commitments to the Sustainable Development Goal 2, which includes improved food security and improved nutrition, and sustainable agriculture [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though there is some spatial variation in the warming signal, most of South Africa has experienced upward trends in temperature during the last half of the 20th century [ 3 , 4 ]. Food security is also under threat, with, for example, crop yields likely to decline in many parts of the country, accompanied by livestock losses [ 5 ]. Furthermore, it is now possible to detect changes in response to climate change in most terrestrial, freshwater and marine ecosystems in the country [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…COP21 United Nations Framework Convention on Climate Change (UNFCCC) meeting in Paris (2015) revealed that many nations are facing food insecurity because of severe climate change hazards. Many scholars have provided a clear evidence of the dangers of climate change (Burke et al 2010; Georgescu, Lobell & Field 2011; Hertel, Burke & Lobell 2010; Lobell et al 2011; Mugambiwa & Tirivangasi 2017; Rowhani et al 2011). Moreover, SADC countries have been affected by water scarcity because of erratic rainfall patterns, increased evaporation and increased water demand in all sectors.…”
Section: Impact Of Climate Change On Food Securitymentioning
confidence: 99%
“…Zimbabwe is particularly vulnerable due to its heavy dependence on rain‐fed agriculture and climate‐sensitive resources (Chagutah, ; Mashizha, Monga, & Dzvimbo, ). Studies conducted in Zimbabwe shows that negative impacts of climate change on crop yields and food production have been far more common than positive impacts (Dzvimbo, Mashizha, Monga, & Ncube, ; Mugambiwa & Tirivangasi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Zimbabwe shows that negative impacts of climate change on crop yields and food production have been far more common than positive impacts (Dzvimbo, Mashizha, Monga, & Ncube, 2017;Mugambiwa & Tirivangasi, 2017).…”
Section: Introductionmentioning
confidence: 99%